Verbal Descriptions of Cue Direction Affect Object Desirability - Tipples, Jason; Dodd, Mike; Grubaugh, Jordan; Kingstone, Alan (Frontiers in Psychology, 2019)
Approach-avoidance behaviours are observed across a broad range of species. For humans, we tend move toward things we like, and away from things we dislike. Previous research tested whether repeatedly shifting visuo-spatial attention toward an object in response to eye gaze cues can increase liking for that object. Here, we tested whether a gaze-liking effect can occur for verbal descriptions of looking behavior without shifts of attention. Also, we tested the gaze specificity hypothesis – that the liking effect is specific to gaze cues – by comparing the effect of different types of cue (pointing gestures and arrow cues). In Experiment 1, participants (N = 205) were split into 5 groups according to the type of cue that was described as directed either toward or away from an object. The results show that 1) attention is not necessary; the liking effect was recorded for verbal descriptions of looking 2) the effect also occurs for descriptions of pointing and arrows and 3) the liking effect is enhanced for gaze cues compared to arrows, consistent with the gaze specificity hypothesis. Results from a further experiment suggest that the effect is not due to demand compliance. We conclude that the gaze-liking effect occurs for verbal descriptions of eye gaze. Indeed, because our method bypasses altogether the use of visual cues, objects, and shifts in visual selective attention, our paradigm appears to be more sensitive at tapping into the fundamental approach-avoidance response that mediate the implicit liking effect. As such, it offers new opportunities for research investigations in the future.